Perlindungan Hukum terhadap Pemilik Tanah Terkait Sengketa Kompensasi yang Dibayar Tidak Sesuai dengan Luas Tanah Bagi Pembangunan Jalan Tol - Andrea Rahmadani; Yurisa Martanti; Khoirul Anwar (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The construction of toll roads in Indonesia often causes land acquisition disputes, especially related to compensation for remaining land that is no longer productive. Although Article 65A paragraph (1) of Government Regulation No. 39 of 2023 provides the right for the community to demand compensation for the remaining land, practice on the ground shows a discrepancy between normative rights and the realization of compensation. This research uses a normative legal approach with legislative, conceptual, analytical, and case study methods, and refers to Dean G. Pruitt's Dispute Resolution Theory and Philipus M. Hadjon's Legal Protection Theory. The results of the study show that the non-litigation resolution mechanism (problem solving) is often ineffective due to the lack of education and facilitation from the authorities, so that people tend to take the path of litigation (contending) to fight for their rights. This condition reflects the weak legal protection for people affected by national strategic projects. Therefore, it is necessary to strengthen legal education for the community and revise Government Regulation No. 39 of 2023 to include compensation for the remaining land that has lost its use value. This revision is important to ensure substantive justice and prevent the escalation of disputes. This research contributes to the development of a more responsive and equitable land acquisition policy, as well as encourages synergy between regulations, education, and effective dispute resolution mechanisms in the context of national infrastructure development.